Valorization of Waste Polyethylene Terephthalate as a Functional Binder for Ballpoint Pen Ink: A Circular Economy Approach - Ri Myong Kim; Jun Hyok Oh; Il Song Ryang; Jong Nam Kim; Yong Il Kim; Guk Chan Kim; Kuang Min Ho; Kum Hyok Ju; Ryong Chol Son (Journal of Chemical Engineering Research Progress, 2026)
The global accumulation of polyethylene terephthalate (PET) waste poses a serious environmental challenge, and the stationery industry remains dependent on virgin petrochemical binders for ballpoint pen inks. This study presents a sustainable upcycling approach that converts waste PET into a functional ink binder. PET bottles were chemically depolymerized via glycolysis with glycerol using zinc acetate as a catalyst. The reaction conditions were systematically optimized, yielding the following optimal parameters: a PET-to-glycerol mass ratio of 1:1.1, 0.6 wt% catalyst, 230 °C, and 4 hours of reaction time. The resulting oligomeric resin (number-average molecular weight, Mn ≈ 1,800 g/mol) was confirmed by FT-IR, GPC, and HPLC. The depolymerization product was formulated into a black ballpoint pen ink with nigrosine dye as the colorant and phenol as the solvent. The optimal formulation (binder:phenol:nigrosine = 7:2:1, plus 0.8 wt% Span-80) exhibited excellent performance: appropriate viscosity, a drying time of ≤19 seconds, reliable temperature resistance from –20 to 40 °C, strong UV resistance of ≥72 hours, and extended storage stability of ≥340 days. All properties met or exceeded industry standards. This work demonstrates a practical, cost-effective, and sustainable route for upcycling PET waste into a high-value stationery product, reducing plastic pollution while replacing petrochemical binders. Copyright © 2026 by Authors, Published by Universitas Diponegoro and BCREC Publishing Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).